Some issues of the use of the institute of mediation in criminal proceedings - Smatlaev Б.М.; Daurembekov Е.К. (BULLETIN of L.N. Gumilyov Eurasian National University Law Series, 2023)
The article focuses on the process of resolving conflict situations and various disputes in pre-trial criminal proceedings in Kazakhstan considering the concept of the legal policy of the Republic of Kazakhstan and a number of other most important strategic state programs aimed at improving criminal and criminal procedure legislation. In this regard, any attempts to resolve disputes that have arisen at the initial stage between the parties protecting the rights and legitimate interests are relevant. So that, there is a procedural need to apply the institute of mediation. The process of implementing this institution required certain efforts and step-by-step reception into national legislation, in order to resolve conflict situations and disputes without bringing them to trial, as well as partially reducing the burden on the judicial system as a whole. In this direction, there is a need for analysis of the current national legislation at the level of the provisions of the Criminal and Criminal Procedure Code and the Law of the Republic of Kazakhstan “On Mediation”. Based on a comprehensive analysis and generalization of existing regulatory sources, educational, methodological, and scientific literature, and statistical and legal approaches, the content of the article reflects the position of the authors regarding the improvement of criminal procedural mechanisms for the use of the institute of mediation. The above proposals are related to the development of clear procedural mechanisms for the development of the institution of mediation in criminal proceedings in Kazakhstan.